Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Mahasiswa Keperawatan Tingkat Akhir di Fakultas Ilmu Kesehatan Universitas Nasional Jakarta - Rachmawaty, Rachmawaty; Hisni, Dayan; Widowati, Retno (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Anxiety is a disorder that can appear in a variety of physical symptoms in addition to feelings of discomfort, anxiety, fear, worry, and discomfort. Anxiety can affect sleep quality, disrupt the immune system, and increase health risks. The higher the level of anxiety, the greater the impact on the level of stressor in a person. A person suffering from excessive worry can cause a person difficulty falling asleep, often waking up during the rest cycle. Anxiety can make individuals experience sleep disorders. The purpose of this study was to identify the relationship between anxiety levels and sleep quality in final year nursing students at the Faculty of Health Sciences, National University of Jakarta. The research method uses Cross Sectional. The population in the study was students of the final year nursing study program of the Faculty of Health Sciences of National University. Sampling technique using purposive sampling with  sample results of 98 respondents. The instruments  used, namely the HARS and PSQI questionnaires using Fisher Chi-Square  Test analysis, were used to identify the relationship between variables. The results showed that anxiety levels had a significant relationship with sleep quality with a P-Value (0.000). Conclusion: The conclusion of this study, there were students who experienced moderate anxiety levels as much as 50.0% and students who experienced poor sleep quality as much as 71.4%. The results showed that there was a significant relationship between anxiety levels and sleep quality in final year students at the Faculty of Health Sciences, National University of Jakarta. Keywords: Anxiety Level, Sleep Quality, Final Year Student  ABSTRAK Kecemasan merupakan suatu kelainan yang dapat muncul dalam berbagai gejala fisik selain perasaan tidak nyaman, gelisah, takut, khawatir, dan tidak nyaman. Kecemasan dapat mempengaruhi kualitas tidur, menganggu sistem kekebalan tubuh, dan meningkatkan risiko kesehatan. Semakin tinggi tingkat kecemasan, semakin besar dampaknya terhadap tingkat stressor pada seseorang. Seseorang yang menderita rasa khawatir yang berlebihan dapat menyebabkan seseorang kesulitan untuk tertidur, sering terbangun selama siklus istirahat. Kecemasan dapat membuat individu mengalami gangguan tidur. Tujuan penelitian ini untuk mengidentifikasi adanya hubungan tingkat kecemasan dengan kualitas tidur pada mahasiswa keperawatan tingkat akhir di Fakultas Ilmu Kesehatan Universitas Nasional Jakarta. Metode penelitian menggunakan Cross Sectional. Populasi dalam penelitian adalah mahasiswa program studi keperawatan tingkat akhir Fakultas Ilmu Kesehatan Universitas Nasional. Teknik pengambilan sampel dengan menggunakan cara purposive sampling dengan hasil sampel sebanyak 98 responden. Instrumen yang digunakan yaitu kuesioner HARS dan PSQI dengan menggunakan analisis Uji Fisher Chi-Square digunakan untuk mengidentifikasi hubungan antara variabel. Hasil penelitian menunjukan bahwa tingkat kecemasan memiliki hubungan yang signifikan dengan kualitas tidur dengan nilai P-Value (0,000). Kesimpulan penelitian ini, terdapat mahasiswa yang mengalami tingkat kecemasan sedang sebanyak 50,0% dan mahasiswa yang mengalami kualitas tidur buruk sebanyak 71,4%. Didapatkan hasil bahwa terdapat hubungan yang signifikan antara tingkat kecemasan dengan kualitas tidur pada mahasiswa keperawatan tingkat akhir di Fakultas Ilmu Kesehatan Universitas Nasional Jakarta. Kata Kunci: Tingkat Kecemasan, Kualitas Tidur, Mahasiswa Tingkat Akhir